Team Leadership and Trust to Assess Project Performance in Higher Education: An Empirical Study - Ming-Ling Chuang; Alexandra Galli-Debicella; Xiaoqi Han (Journal of Management Research, 2024)
Leaders have a significant role in teams and groups, as they affect employee performance, motivation, and productivity. Given the significant position that leaders occupy in teams and group projects, this paper argues that it is important to simultaneously examine how trust in a leader, team interactions, and team performance interact with each other. Specifically, we formulated three hypotheses: First, we predicted a positive relationship between the level of trust that team members have in their team leader and the level of team performance; second, we predicted a positive relationship between the level of trust in a leader and the level of team interactions; last, we predicted that increased trust in a leader will increase team interactions and team performance. To test the model, we utilized data from 112 MBA students engaged in a web-based simulation game wherein students develop and execute the strategies for manufacturing and distributing a product. We used structural equation modeling to test these hypotheses. Our results support the importance and value of leader trust in team interactions. The results also indicate that team interaction positively influences team performance. However, they do not support our hypothesis that trust in a leader will positively influence team performance.